CHILD GROWTH IN SCHOOL CONTEXTS: A COMPARISON BETWEEN PUBLIC AND PRIVATE NETWORKS (CIPEEX, 2025)
In Brazil, public and private schools present differences that extend beyond the pedagogical sphere, also reflecting on aspects such as health, nutrition, and quality of life. This study aimed to analyze scientific evidence on child growth in different school contexts, comparing public and private institutions. A qualitative literature review was conducted based on nine articles published in national and international journals, retrieved from databases such as BVS and Google Scholar. The review included studies addressing cognition, nutrition, quality of life, public policies, and educational programs. The search was limited to publications from the last ten years, selecting only those most closely related to the research theme. Inclusion criteria: articles in Portuguese, English, or Spanish, available in full text and pertinent to the study’s objective. Exclusion criteria: duplicate articles, abstracts without full access, and those not aligned with the proposed theme. The findings indicate that students from private schools generally show better cognitive and linguistic performance, higher quality of life, and greater adherence to health education programs. Nevertheless, issues related to school nutrition, such as unbalanced menus and childhood obesity, were present in both public and private systems. Structural and policy-related factors were also identified as determinants of the observed inequalities. Inequalities between public and private schools in Brazil go beyond infrastructure, directly impacting children’s learning, health, and overall well-being. It is necessary to invest in public policies that foster equity in both education and health.
Keywords: Child development; Public school; Private school